Increasing Company Value Through Financial Policies and Performance of Manufacturing Companies Listed on The Indonesia Stock Exchange - Adhi Widyakto; Endang Tri Widyarti; Edy Suryawardana (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2021)
The phenomenon that there are still many manufacturing industry companies on the Indonesia Stock Exchange that have a PBV smaller than one is the main basis for conducting the study. This study aims to analyze the effect of financial policy and financial performance on firm value. The sampling technique was based on purposive sampling. The data analysis technique used a linear regression model. Based on the analysis and discussion results, there are four main findings obtained from this study: First, the model used is significant to explain changes in firm value with the ability to explain 48.7 percent. Second, of the five independent variables, there are three variables: the policy in working capital management and the performance variable, namely the volatility of expectations and returns, which have a significant effect. To the value of the company. Third, the company's financial performance factors have a more dominant influence on the company's value dynamics than policy factors. Fourth, the direction coefficient of the influence of the independent variable on the dependent variable, although the two variables are not significant. The practical implication is to increase the value of a manufacturing company. Therefore, it is advisable to consider financial policies and financial performance. Theoretically, financial management based on signal theory and trade-off theory of Islamic perspective theory can increase firm value.